Yerba Mate – a study on the tea from Latin America - Kant, Shashi; Chauhan, Hitendra Singh; Sajwan, Deepika (Journal of Postharvest Technology, 2022)
The purpose of this study is to create awareness among Hospitality Professionals, Tea connoisseurs, students, and researchers of India and neighboring countries about this Tea. Yerba Mate tea, an infusion prepared from the leaves of the Ilex paraguariensis tree. It is a popular non alcoholic beverage in South America that is quickly gaining traction in the international market, either as tea or as a component of prepared foods or nutritional supplements. For ages, the indigenous people have consumed it as a social and therapeutic beverage. Yerba Mate tea is Argentina’s national drink, but it’s also well-known for its energizing, rejuvenating, and weight-loss effects. South American footballers, who appear to carry their mate gourds with them wherever they go, have popularized the drink in Europe. This review focuses on the history, production, and health benefits of Yerba.